MANAGEMENT OF INTERNAL QUALITY ASSURANCE IN CHARACTER EDUCATION - Rakhma Agustina Sulistyowati; Achmad Supriyanto; Mustiningsih Mustiningsih (Pascasarjana UM, 2017)
Abstract: This study aims at describing the internal quality assurance management in character education. This research was a qualitative research using multi-site design study. The data of this research was obtained through observation, interview, and documentation. The data analysis was performed with single site data analysis and cross-site data analysis. The findings of this study were: the implementation of quality assurance of school's vision and mission and the meaning of quality assurance; The establishment of indicators of quality standards and their implementation systems; The implementation of quality standard using activity program; The evaluation of student quality standard by using observation method and self-report; The quality standard control using routine guidance for teachers, guidance for students and SOP changes; The improvement of quality standards with improvements in indicators, quality of human resources and teachers in preparation for improving quality standards.Key Words: internal quality control, SDIT, character educationAbstrak: Penelitian ini bertujuan untuk mendeskripsikan manajemen penjaminan mutu internal dalam pendidikan karakter. Penelitian ini merupakan penelitian kualitatif dengan menggunakan rancangan studi multi situs. Data untuk penelitian ini didapatkan melalui observasi, wawancara, dan dokumentasi. Analisis data dilakukan dengan situs tunggal data analisis dan analisi data lintas situs. Temuan dari penelitian ini adalah: implementasi penjaminan mutu visi dan misi sekolah dan arti penjaminan kualitas; pembentukan indikator standard mutu dan sistem pelaksanaanya; pelaksanaan standard mutu menngunakan program aktifitas; evaluasi standard mutu siswa dengan menggunakan metode observasi dan lapor diri; pengendalian standar mutu menggunakan pembinaan rutin untuk guru, bimbingan untuk siswa dan perubahan SOP; peningkatan standar mutu dengan peningkatan indikator, kualitas sumber daya manusia dan guru dalam persiapan peningkatan standar mutuKata kunci: penjaminan mutu internal, SDIT, pendidikan karakter